Transformasi Tradisi Pacu Kuda Gayo Pada Era Parawisata Takengon - Qanitatul Isra Qamal; Luthfia Cinta Mulyani; Iqbal Rahimsyah; Nurul Fajri; Muhammad Ryan Harvany Chan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Gayo Horse Racing tradition, which originated around 1850 on the shores of Lake Laut Tawar, initially functioned as post-harvest entertainment and a symbol of social status for the Gayo community in Central Aceh. This study aims to analyze the transformation of this tradition in the era of Takengon tourism, where annual events held in August and February have become festivals attracting both national and international tourists. Using a qualitative ethnographic approach, data were collected through participant observation during the 2025 festival and in-depth interviews with informants. The main findings indicate a transformation from a communal ritual into a tourism commodity: a modern oval track at Gelenggang Musara Alun has been established, child jockeys riding without saddles are still maintained, while Australian–Gayo crossbred horses dominate due to their speed, resulting in positive economic impacts such as an increase in traders’ income of up to 300% during the event. The implications of this study include the preservation of cultural identity through sustainable tourism regulations, contributions to ethnographic tourism studies in Indonesia, and policy recommendations to minimize negative impacts such as gambling.